2021
DOI: 10.1159/000520326
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oropharyngeal Dysphagia and Risk of Pneumonia, Malnutrition, and Mortality in Adults Aged 60 Years and Older: A Meta-Analysis

Abstract: <b><i>Introduction:</i></b> Oropharyngeal dysphagia (OD) is a serious health condition associated with poor survival and quality of life in adults aged 60 years and older. Comprehensive assessment and management of OD could lead to better and improved health outcomes for older adults. Therefore, we performed the first meta-analysis to determine the pooled prevalence of OD and risk of pneumonia, malnutrition, and mortality. <b><i>Methods:</i></b> Databases includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…We found a substantial prevalence of OD estimated at 35%, with a 6.41 times risk of mortality among hospitalized COVID-19 patients. Previous study findings have shown a higher prevalence rate of OD in post-extubated critically ill patients, acute stroke patients, and older adults, with prevalence rates being closer to 50% [ 4 , 5 , 34 ]. McIntyre et al [ 34 ] found an incidence rate of 41% for OD among hospitalized critically-ill patients secondary to intubation, while the prevalence of OD has been estimated at 42% among acute stroke patients [ 4 ] and 46% among older adults [ 5 ].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…We found a substantial prevalence of OD estimated at 35%, with a 6.41 times risk of mortality among hospitalized COVID-19 patients. Previous study findings have shown a higher prevalence rate of OD in post-extubated critically ill patients, acute stroke patients, and older adults, with prevalence rates being closer to 50% [ 4 , 5 , 34 ]. McIntyre et al [ 34 ] found an incidence rate of 41% for OD among hospitalized critically-ill patients secondary to intubation, while the prevalence of OD has been estimated at 42% among acute stroke patients [ 4 ] and 46% among older adults [ 5 ].…”
Section: Discussionmentioning
confidence: 98%
“…Growing evidence revealed oropharyngeal dysphagia (OD) as one of the digestive complications among hospitalized COVID-19 patients. Moreover, OD has been shown to be highly correlated with a risk of aspiration pneumonia, malnutrition, and mortality in acute stroke and older adults without COVID-19 [ 4 , 5 ]. Exploring and understanding the prevalence of OD in COVID-19 patients would provide plausible evidence crucial for the management of COVID-19-associated OD in clinical settings.…”
mentioning
confidence: 99%
“…Additionally, we surveyed caregivers about their attention to feeding tubes and the eating habits of their care receivers. The caregivers were asked to provide multiple responses from among the following items 1 : preparation of a suitable diet for swallowing function; 2 nutritional balance of dietary intake; 3 assistance with eating; 4 time required for meals and feeding tubes; 5 number of meals per day; 6 oral exercise before mealtimes; 7 supervision during mealtime and feeding tube; 8 oral care; 9 aspiration and choking; 10 reflux and vomiting after meals and feeding tube; 11 nutrition status; and 12 fever and increased sputum production.…”
Section: Methodsmentioning
confidence: 99%
“…Dysphagia, a medical condition commonly caused by stroke, neuromuscular disease or head and neck cancer, has a reported prevalence of 40–81% among individuals with chronic stroke, 9 82% among those with Parkinson's disease, 10 and 38.5% among those with head and neck cancer 11 . Because dysphagia can lead to adverse events, such as aspiration pneumonia, choking and malnutrition, 12 it has been speculated that dysphagia might contribute to the exacerbation of caregiver burden. In fact, 71% of caregivers of patients with dysphagia have experienced caregiver burden, 13 which is multifaceted, and includes physical, mental 14 and emotional burden 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies reported that aspiration pneumonia is associated with dysphagia [ 5 , 6 ] and sarcopenia [ 7 ]. Based on the deep relationship between them [ 8 ], which is related to declining activities of daily living (ADL) [ 9 , 10 ] and increased mortality [ 11 , 12 ], improving dysphagia and sarcopenia is important for improving the prognosis of older inpatients with aspiration pneumonia.…”
Section: Introductionmentioning
confidence: 99%